A General Framework for Treatment Effect Estimators Considering Patient Adherence. (2nd January 2020) - Qu, Yongming; Fu, Haoda; Luo, Junxiang; Ruberg, Stephen J.
Abstract: Randomized controlled trials remain a gold standard in evaluating the efficacy and safety of a new treatment. Ideally, patients adhere to their treatments for the duration of the study, and the resulting data can be analyzed unambiguously for efficacy and safety outcomes. However, some patients may discontinue the study treatment due to intercurrent events, which leaves missing observations or observations that do not reflect the randomly assigned treatment. Frequently, an intent-to-treat analysis (or a modification thereof) is done to estimate the treatment effect for all randomized patients regardless of the occurrence of intercurrent events. Alternatively, clinicians may be more interested in understanding the efficacy and safety for those who can adhere to the study treatment. The naive per-protocol analysis may provide a biased estimate for the treatment difference because the observed adherence populations may not be comparable between two treatments. In this article, we propose two methods for estimation of the treatment difference for those who can adhere to one or both treatments based on the counterfactual framework. Theoretical derivations and a simulation study show the proposed methods provide consistent estimators for the treatment difference for the adherent population of interest. A real data example comparing two basal insulins for patients with type-1 diabetes is provided using the proposed methods. Supplementary materials for this article are available online.